ANALISIS KAPASITAS DUKUNG FONDASI GEDUNG PELAYANAN UMUM DAN KEMAHASISWAAN POLITEKNIK KESEHATAN GORONTALO BERDASARKAN DATA SONDIR - Bumulo, Ronny; Madjowa, Nona Fitriana; Ismail, Rahmad Wahyudi (Universitas Bina Taruna Gorontalo, 2022)
The Research objectives are to achieve the foundation support capacity of the wells by referring to the sample of sondir data research conducted by the UNG laboratory. It is located in Moodu village, East city district, Gorontalo city. The research method used quantitative methods by recalculating the burden that can be borne by the foundation of the well.the soil conditions in Gorontalo Province, especially Gorontalo, are of clay type soil. In this study, the secondary data was take from quantitative methods where the relevant agencies concern to the form of sondir data. To process it, the writer uses 2 analytical equations to calculate the bearing capacity of the well foundation. Through put processing, it will get some results that usefull as a reference for the construction of the building. Then, it makes the results are more accurate. Based on the evaluation results, the construction of this building at point 1 with a depth of 2.80 m and a diameter of 1.20 m is 209.67 tons - 219.23 tons, while at point 2 with a depth of 2.80 m and a diameter of 1.20 m is 186.79 tons - 198.23 tons.